Effectiveness of the PERMAJA Educational Program in Enhancing Adolescent Reproductive Health Knowledge During Disasters - Ayu Istiada; Alfiana Ainun Nisa; Nugroho, Efa; Rachmawati, Latifah (Universitas Airlangga, 2025)
Background: Adolescents are among the most vulnerable groups during disasters, often facing an increased risk of sexual violence, poverty, and other reproductive health threats. These risks are exacerbated by the lack of private spaces for changing clothes, unsecured shelters, and shared toilet facilities for males and females in evacuation areas. Objective: This study aims to assess adolescents' knowledge of reproductive health in disaster situations and to develop empowerment activities through the PERMAJA (Peduli Kespro Masa Remaja) program. Methods: A quantitative descriptive study with a cross-sectional design was conducted involving 160 adolescents from three flood-prone areas in Central Java: Grobogan, Demak, and Semarang. The study was carried out from July to September 2024. Data were collected using a structured questionnaire and analyzed using univariate analysis to measure changes in knowledge before and after the educational intervention. Results: The findings showed an increase in adolescents' understanding of reproductive health during disasters following the educational sessions. The average score rose from 6.28 in the pre-test to 6.34 in the post-test. Although the increase in average scores was modest, the variation in responses indicated a broader comprehension of the topic among participants. Conclusion: The PERMAJA initiative contributed positively to enhancing adolescents' knowledge of reproductive health in disaster contexts. The program demonstrates the potential of targeted education in empowering vulnerable youth populations, particularly in high-risk disaster-prone areas.